Immunotherapy for Hepatocellular Carcinoma: Current Status and Future Prospects - Liu, Zhuoyan; Liu, Xuan; Liang, Jiaxin; Liu, Yixin; Hou, Xiaorui; Zhang, Meichuan; Li, Yongyin; Jiang, Xiaotao (Frontiers in Immunology, 2021)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer with poor prognosis. Surgery, chemotherapy, and radiofrequency ablation are three conventional therapeutic options that will help only a limited percentage of HCC patients. Cancer immunotherapy has achieved dramatic advances in recent years and provides new opportunities to treat HCC. However, HCC has various etiologies and can evade the immune system through multiple mechanisms. With the rapid development of genetic engineering and synthetic biology, a variety of novel immunotherapies have been employed to treat advanced HCC, including immune checkpoint inhibitors, adoptive cell therapy, engineered cytokines, and therapeutic cancer vaccines. In this review, we summarize the current landscape and research progress of different immunotherapy strategies in the treatment of HCC. The challenges and opportunities of this research field are also discussed.